Feminist Judging in the 'Real World' - Hunter, Rosemary C. (Oñati Socio-Legal Series, 2018)
The various feminist judgment projects (FJPs) have explored through the imagined rewriting of judgments a range of ways in which a feminist perspective may be applied to the practice of judging. But how do these imagined judgments compare to what actual feminist judges do? This article presents the results of the author’s empirical research to date on ‘real world’ feminist judging. Drawing on case study and interview data it explores the how, when and where of feminist judging, that is, the feminist resources, tools and techniques judges have drawn upon, the stages in the hearing and decision-making process at which these resources, tools and techniques have been deployed, and the areas of law in which they have been applied. The article goes on to consider observed and potential limits on feminist judicial practice, before drawing conclusions about the comparison between ‘real world’ feminist judging and the practices of FJPs.